Forest structures across Europe. (23rd May 2017) - Moreno, A.; Neumann, M.; Hasenauer, H.
Abstract : Pan‐European gridded datasets derived from a single methodology to inform researchers, policy makers and conservationists on the state of forest structures would improve our ability to study forests independent of political boundaries and along various gradients. Although National Forest Inventory (NFI) data provide information on the characteristics of forests, including carbon content, volume, height, and age, such spatial data is not available across Europe. Before this study, remotely sensed data covering all of Europe had not been utilized to produce multiple European‐focused forest structure datasets over the entire continent that are methodologically consistent and comparable. We used existing European data to develop a pan‐European dataset covering tons of live tree carbon and volume per hectare, mean tree height and mean tree age by integrating remotely sensed and harmonized NFI data from 13 different European countries. We produced a pan‐European map for each of the four key variables on a 0.133° grid representing the time period 2000–2010.